The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.2147/ceor.s108288
|View full text |Cite
|
Sign up to set email alerts
|

Disease progression and health care resource consumption in patients affected by hepatitis C virus in real practice setting

Abstract: IntroductionHepatitis C virus (HCV) infection represents serious health problems worldwide and is a major contributor to end-stage liver disease including cirrhosis and hepatocellular carcinoma (HCC). In Italy, ~2% of subjects are infected with HCV. The objective of this study was to describe treatment patterns, disease progression, and resource use in HCV.MethodsAn observational retrospective cohort analysis based on four Local Health Units administrative and laboratory databases was conducted. HCV-positive p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…10 Our findings are in line with a recently published nationwide study, which used the same methods of analysis as ours in a real-world clinical setting. The study conducted by Perrone et al, 12 from 2009 to 2010, showed that the prevalence of HCV among ~2.5 million health-assisted individuals was 0.4%. The recent study conducted by Lapi et al, analyzing all outpatients aged at least 15 years registered in the Italian Health Search IMS Health Longitudinal Patient Database from January 1, 2002 to June 30, 2013 reported that the prevalence rate of HCV in the 11-year study period was in the range from 0.24% to 0.50%.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…10 Our findings are in line with a recently published nationwide study, which used the same methods of analysis as ours in a real-world clinical setting. The study conducted by Perrone et al, 12 from 2009 to 2010, showed that the prevalence of HCV among ~2.5 million health-assisted individuals was 0.4%. The recent study conducted by Lapi et al, analyzing all outpatients aged at least 15 years registered in the Italian Health Search IMS Health Longitudinal Patient Database from January 1, 2002 to June 30, 2013 reported that the prevalence rate of HCV in the 11-year study period was in the range from 0.24% to 0.50%.…”
Section: Discussionmentioning
confidence: 99%
“…At any rate, our findings are consistent with those of other Italian studies under real-world circumstances, in the literature so far. 12 , 31 Stroffolini et al showed that only 33% of evaluated HCV-infected patients were treated with current standard of care for hepatitis C. 31 A recent retrospective Italian study revealed that 12 patients who have not received HCV treatments showed a higher rate of progression of disease than patients who underwent therapy; in addition, these results also showed that patients receiving no treatment led to an increase in health care resources, especially in terms of hospitalizations. Providing early appropriate therapeutic interventions that can prevent liver disease progression related to HCV can potentially further reduce the economic burden associated with chronic hepatitis infection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The structure of these DBs, which are routinely updated for administrative and reimbursement purposes, has been described in detail elsewhere. 12 The following DBs were used in this study: the beneficiaries DB, which contains patient demographic data; the medication prescription DB, which comprises information, including the Anatomical-Therapeutic-Chemical code, number of packages ordered, number of units per package, dosages, unit cost per package, and prescription date for each drug purchased for the patient; the hospital discharge DB, which contains data regarding all hospitalizations and includes the discharge diagnosis codes (classified according to the International Classification of Diseases, Ninth Revision, Clinical Modification [ICD-9-CM]) and diagnosis-related group (DRG) reimbursement rate; and the ambulatory care specialist DB, which includes records for all outpatient specialist services provided to the patient. The DBs were linked via anonymized patient codes.…”
Section: Methodsmentioning
confidence: 99%
“…Italy, Romania, Spain, Germany, France, United King-dom, Poland, Greece, and Bulgaria are the countries in which there are more than 80% of the patients affected by HCV in Europe (2). Currently, a small number of data sets are available on the epidemiology of HCV infection in Italy (3)(4)(5)(6). However, the known data demonstrate a prevalence of seropositivity for HCV that is higher in the Southern areas (7.3%), Central island (6.1%), and Northern ones (about 1.6%) (4).…”
Section: Introductionmentioning
confidence: 99%